THE EFFECT OF UTILIZING ASSEMBLR ON STUDENTS’ READING INTEREST IN 5TH GRADE STUDENTS OF SDIT WIDYA CENDEKIA - Hilman Hilman; Abdul Muin Bahaf; Dede Irma; Ulhiyati Ulhiyati; Wulan Maharani; Ihsan Maulana Febriani; Dami Dami; Silvia Ayu Tri Andini (LPPM Universitas Bina Bangsa, 2023)
This study aims to determine the reading interest of grade 5 students at SDIT Widya Cendekia before and after using assemblr media, and to determine the influence of Assemblr media on reading interest of grade 5th students at SDIT Widya Cendekia. This type of research is quantitative using experimental research methods with the form of pre-experimental research type one group pre-test post-test design. The population in this study were 16 bilingual 5th-grade students at SDIT Widya Cendekia AY 2022/2023. The sampling technique used is saturated sampling because the population is relatively small, namely less than 30. The number of samples used is the entire population, namely 16 students. Data collection techniques are observation, interview, questionnaires, and literature. Based on the results of the analysis, The average of each indicator and the pre-test and post-test results show that students' learning interest has increased. Additionally, in tests, it explains why the t-distribution table's pre-test stage and post-test stage t-values are 2.81 and 2.131, respectively, with a significance value of 0.000 < 0.05. According to the decision-making foundation in the sample t-pairs, it can be deduced from the -table > t-value that Ha was accepted and Ho was denied, indicating that there was a connection between the usage of augmented reality media and students' interest in reading at SDIT Widya Cendekia